Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1073/pnas.80.19.6136
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride reduces the taste intensity of Na+ and Li+ salts and sweeteners.

Abstract: The diuretic amiloride, a potent inhibitor of sodium transport in a variety of epithelial systems, was applied to the human tongue. Application of amiloride reduced the taste intensity of sodium and lithium salts and of sweeteners ranging widely in chemical structure. The sweeteners included saccharides, glycosides, dipeptides, proteins, and amino acids. Amiloride did not affect perception of potassium or calcium salts, bitter and sour tastes, or amino acids without a sweet or salty component. These findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(116 citation statements)
references
References 19 publications
6
108
1
Order By: Relevance
“…The sodium-selective ion channels, or epithelial sodium channels (ENaCs), expressed by these cells can be blocked with the drug amiloride (see Brand, Teeter, & Silver, 1985;DeSimone & Ferrell, 1985;Doolin & Gilbertson, 1993;Heck, Mierson, & DeSimone, 1984;Schiffman, Lockhead, & Maes, 1983). A second transduction pathway for sodium, the amiloride-insensitive (AI) pathway, is not sodium selective but instead appears to be activated by a variety of cations, including Na ϩ , K ϩ , and NH 4 ϩ (Brand et al, 1985;DeSimone & Ferrell, 1985;Kloub, Heck, & DeSimone, 1997;Ye, Heck, & DeSimone, 1994).…”
mentioning
confidence: 99%
“…The sodium-selective ion channels, or epithelial sodium channels (ENaCs), expressed by these cells can be blocked with the drug amiloride (see Brand, Teeter, & Silver, 1985;DeSimone & Ferrell, 1985;Doolin & Gilbertson, 1993;Heck, Mierson, & DeSimone, 1984;Schiffman, Lockhead, & Maes, 1983). A second transduction pathway for sodium, the amiloride-insensitive (AI) pathway, is not sodium selective but instead appears to be activated by a variety of cations, including Na ϩ , K ϩ , and NH 4 ϩ (Brand et al, 1985;DeSimone & Ferrell, 1985;Kloub, Heck, & DeSimone, 1997;Ye, Heck, & DeSimone, 1994).…”
mentioning
confidence: 99%
“…As far as has been tested, all sources of saltiness cross-adapt in human subjects (Bartoshuk & Dember, 1988;McBurney & Lucas, 1966;Smith & McBurney, 1969). Amiloride, a sodium channel blocker, originally appeared to block salty tastes in human subjects (Schiffman, Lockhead, & Mars, 1983), but later work failed to confirm this observation (Desor & Finn, 1989).…”
Section: Saltymentioning
confidence: 98%
“…The diuretic agent amiloride, a sodium channel blocker, selectively suppresses taste responses to NaCl, but not to sweet, sour, and bitter substances in many mammals (Schiffman et al, 1983, Heck et al, 1984, Jakinovich 1985, Simon et al, 1986, Herness 1987, Ninomiya et al, 1989, Hellekant and Ninomiya, 1991. Subsequent studies using amiloride in rodents suggested that two distinct components underlie cellular sensitivity to NaCl: one that is amiloride-sensitive and another that is amilorideinsensitive.…”
Section: Neural and Molecular Mechanisms Of Salt Taste Perceptionmentioning
confidence: 99%
“…Psychophysical studies in humans have shown that taste intensity for Na + and Li + salts is also suppressed by amiloride treatment (Schiffman et al, 1983). Genetic variants in ENaC (βENaC (G442V) or αENaC (T663A)) relate to aldosterone and potassium excretion and risk for hypertension (Ambrosius et al, 1999).…”
Section: Neural and Molecular Mechanisms Of Salt Taste Perceptionmentioning
confidence: 99%
See 1 more Smart Citation